2003
DOI: 10.1212/01.wnl.0000103900.65021.5b
|View full text |Cite
|
Sign up to set email alerts
|

Urgent endovascular revascularization for symptomatic intracranial atherosclerotic stenosis

Abstract: Endovascular revascularization of intracranial vessels is technically feasible and may be performed successfully. However, periprocedural complication and fatality rates in neurologically unstable patients are high. The results suggest that patient selection, procedure timing, and periprocedural medical management are critical factors to reduce periprocedural morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 26 publications
2
73
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] In the present study, TAS for occluded lesions was shown to be technically feasible with a high success rate, similar to treatment of stenotic lesions. Technical success in treating the occluded lesion depends on the freshness of the occluded clots and the occluded segment being short enough for the microguidewire to pass through it; such conditions are frequently encountered in the acute stroke stage.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10] In the present study, TAS for occluded lesions was shown to be technically feasible with a high success rate, similar to treatment of stenotic lesions. Technical success in treating the occluded lesion depends on the freshness of the occluded clots and the occluded segment being short enough for the microguidewire to pass through it; such conditions are frequently encountered in the acute stroke stage.…”
Section: Discussionsupporting
confidence: 54%
“…Angioplasty and/or stent placement for the IVBA are becoming increasingly common, [1][2][3][4][5][6][7][8][9][10] and recanalization therapy with angioplasty and/or stent placement has been reported anecdotally for the IVBA, even in the acute stroke stage. 4,10 However, most case series have included patients of varied background: patients in acute and chronic stroke stages 4 or acute stroke patients with lesions of the anterior circulation. 10 Therefore, the clinical features and outcome in acute ischemic stroke patients who underwent transluminal angioplasty and/or stent placement (TAS) performed within 7 days after stroke onset for occlusive lesions of the IVBA are not well established, and the problems associated with TAS in clinical practice have not been determined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data on angioplasty and stent placement in the acute phase of ischemic stroke are limited [50][51][52] . Angioplasty and stenting have been used to treat acute stroke secondary to carotid artery dissection 53 .…”
Section: Angioplasty and Stentingmentioning
confidence: 99%
“…34 Angioplasty has been the most common endovascular therapy for intracranial stenosis and may have some ability to reduce the risk of stroke in selected patient populations, with an annual stroke rate of 3.36%. [35][36][37] Studies of endovascular therapy show that stent placement can be performed with high success and low adverse event rates within the MCA and that stent placement reduces residual postoperative stenosis compared with angioplasty.…”
Section: Risk Management and Outcomesmentioning
confidence: 99%